Optimal post-breeding interval for pregnancy diagnosis in mares by using ultrasonographic technique: Omran, S. N. 1and Rasheed Y. M. - M., Rasheed Y. (The Iraqi Journal of Veterinary Medicine, 2013)
The present study was conducted in two different farms, including (256) foaling mares in : AL-Laith equine herd and equestrian club in AL-Ameria, 4-14 years old foaling mares which are situated in areas around Baghdad and extended one calendar from July 2011 until July 2012 . These mares were examined for pregnancy diagnosis by trans-rectal ultrasonography using a 5 MHz lineararray transducer between Days 10 and 40 after breeding (breeding day = Day 0). Criteria to assess the accuracy of trans-rectal sonography were overall accuracy (correct diagnoses/all diagnoses), sensitivity (correct diagnoses "pregnant"/all pregnant animals), and specificity (correct diagnoses "non-pregnant" /all non-pregnant animals. The sensitivity, specificity and accuracy of trans-rectal ultrasonography were 91.4%, 96.2% and 94.7%, respectively, around day (10-40). Accuracy, Sensitivity and Specificity of pregnancy diagnosis were superior (97.8%, 95.2% and 100%), respectively, in (31 - 35) day post breeding (P< 0.01). The results of this study showed a significant difference (P<0.01) in the parameters of sensitivity and various post-breeding intervals. The results of the present study revealed that using trans-rectal ultrasound for pregnancy diagnosis in mares could be used and are reliable under field conditions from day (31) of Gestation onward